Understanding self and peer assessment processes: Developments in an EAP module for academic reading and oral presentation skills - Schrader, Karen (2015)
Abstract Self-assessment and peer-assessment in higher education aim to develop the student’s ability for life-long learning beyond the confines of a formalized university setting. These two types of formative assessment have been found conducive to language learning contexts and can increase student motivation and self-regulated learning through directed self-reflection and collaborative learning situations. A successful implementation requires critical understanding of the processes. This action research dissertation explores a group of teachers’ (N=5) collaborative effort to introduce written self-reflection and peer-feedback in a revised English for Academic Purposes reading and oral presentation module. A mixed-method, action research approach using focus group interviews and questionnaires was used to gather insights into best practices as well as impressions of the benefits, limitations and improvements in oral presentation skills. The data from the teachers was triangulated with results from a student survey of my two classes (N=31). The results revealed that both stakeholder groups were overall satisfied with the learning outcomes and felt that the selfassessment and peer-assessment tasks were worthwhile and rewarding. Further, the findings illustrate that detailed, accessible explanations, adequate training, use of video and awarding marks for the quality of the assignments were processes that led to a smooth and successful implementation of self- and peerassessment. However, the teachers found more scaffolding in the form of guiding questions and more emphasis on critical reading and language skills are necessary to complete the learning goals. I offer recommendations for future improvements to the four phases of the formative assessment process: introduction, training, implementation and follow-up, which can be used as a basis for future teachers.